Decontamination of seawater from 137Cs and 90Sr radionuclides using inorganic sorbents. (June 2020) - Voronina, A.V.; Noskova, A. Yu; Semenishchev, V.S.; Gupta, D.K.
Abstract: In this work, we have studied sorption of 137 Сs and 90 Sr radionuclides from seawater under batch conditions by ferrocyanide sorbents based on hydrated titanium and zirconium dioxides (Т-35, NPF-HTD), clinoptilolite and glauconite (NPF-GL, NPF-CL) natural aluminosilicates, zirconium phosphate (T-3A), modified hydrated titanium dioxide (T-3K) as well as by manganese dioxide based on hydrated titanium dioxide (MD-HTD). Isotherms of sorption and dependences of cesium distribution coefficients on salt content and calcium concentration were obtained. Distribution coefficients of cesium and strontium were calculated. Stability of spent sorbents against radionuclides leaching was studied in from the point of view of their further treatment. The NPF-GL and NPF-HTD sorbents are recommended for treatment of seawater-based liquid radioactive waste with various salinity; these sorbents possess high distribution coefficients of cesium 10 4 and 10 5  ml/g even at the salinity of waste as high as 100 g L −1 . Distribution coefficients of strontium from seawater were (1.0–1.9)·10 2  ml/g for all sorbents that is conditioned by the presence of colloidal species of strontium (34 ± 7%) in the simulated seawater. Capacities of the sorbents for strontium varied within 200–310 mg/g. The sorbents strongly retain adsorbed radionuclides: the total percentage of leaching for 28 days was 4.4%, 2.2% and 3.1% for 137 Cs leaching from the NPF-HTD, T-35 and T-3A sorbents respectively and 10.7% for 90 Sr leaching from the NPF-CL sorbent. Highlights: Seven inorganic sorbents were tested for deactivation of seawater. Sorbents based on ferrocyanides are suitable for cesium separation from seawater. Strontium separation is complicated because of high salt content. NPF-HTD and NPF-CL sorbents provide irreversible sorption and low leaching degrees.